2018
DOI: 10.3390/app8091526
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric Materials: A Novel Pathway for Efficient Solar Water Splitting

Abstract: Over the past few decades, solar water splitting has evolved into one of the most promising techniques for harvesting hydrogen using solar energy. Despite the high potential of this process for hydrogen production, many research groups have encountered significant challenges in the quest to achieve a high solar-to-hydrogen conversion efficiency. Recently, ferroelectric materials have attracted much attention as promising candidate materials for water splitting. These materials are among the best candidates for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 208 publications
(276 reference statements)
0
22
0
Order By: Relevance
“…Perovskite structure of bismuth ferrite (BiFeO 3 ) has been emerged as a visible light active photocatalyst with band gap of 2.0 to 2.7 eV, good chemical stability, photoelectric, and ferromagnetic features at room temperature. 15,16,[43][44][45][46][47] Most of the research done on BFO is related to water treatment and according to our studies, no research has been found related to water splitting by CdS/BFO heterojunction. When CdS and BiFeO 3 (BFO) combine together, it is expected that there is easy Z-scheme charge transfer, thereby enhancing charge separation and promoting the photocatalytic activity of H 2 evolution from water splitting.…”
Section: Introductionmentioning
confidence: 64%
“…Perovskite structure of bismuth ferrite (BiFeO 3 ) has been emerged as a visible light active photocatalyst with band gap of 2.0 to 2.7 eV, good chemical stability, photoelectric, and ferromagnetic features at room temperature. 15,16,[43][44][45][46][47] Most of the research done on BFO is related to water treatment and according to our studies, no research has been found related to water splitting by CdS/BFO heterojunction. When CdS and BiFeO 3 (BFO) combine together, it is expected that there is easy Z-scheme charge transfer, thereby enhancing charge separation and promoting the photocatalytic activity of H 2 evolution from water splitting.…”
Section: Introductionmentioning
confidence: 64%
“…The use of photoferroic materials for PEC can improve the efficiency of these devices, by generating large photovoltages that can more easily provide the required energy to overcome all the losses and overpotentials, while still harvesting a significant fraction of the solar energy. Experiments have already pioneered the use of photoferroics in PEC devices, as highlighted in a recent review [117]. It has been shown, for example, that the separation of charges can be enhanced in materials like PbTiO 3 thanks to their intrinsic ferroelectricity [118,119].…”
Section: Discussionmentioning
confidence: 99%
“…Experiments have already pioneered the use of photoferroics in PEC devices, as highlighted in a recent review. [109] However most of the materials investigated have a band gap close to the UV part of the spectrum and thus absorbs only a small fraction of the solar energy. The unique combination of ferroelectric and optical properties opens the door to the development of multisource energy harvesting or multifunctional sensing devices for the simultaneous and efficient conversion of solar, thermal, and kinetic energies into electricity in a single material.…”
Section: Discussionmentioning
confidence: 99%
“…Photoferroic materials that combine ferroelectric and lightharvesting properties are promising for optoelectronic applications like photovoltaics 1,2 or photo(electro)chemical water-splitting. 3 The spontaneous polarization of ferroelectrics can be reversed by the application of an external electric field with potential benefits for photoelectrocatalytic water splitting. 4−7 Due to the strong internal electric field induced by the spontaneous electric polarization, the photogenerated electrons and holes migrate in opposite directions, which enhances charge-carrier separation and promotes photocatalytic properties.…”
Section: ■ Introductionmentioning
confidence: 99%